Netflix, nostalgia and transnational television. Issue 3 (1st October 2021) - Jenner, Mareike
This article offers an overview of the various kinds of nostalgia Netflix engages with. The focus here is self-produced originals and the way nostalgic elements are used to create different kinds of political outlooks within a transnational television environment. An underlying question is: in what ways can nostalgia be political within the transnational context of Netflix? The article explores this question while giving an overview of nostalgia's use in different series, such as the culturally regressive politics of The Crown (2016‐present), the progressive social justice project of Sex Education (2019‐present) and the semiotic (if not political) project in series like Bridgerton (2020‐present).